The Effect of Video Learning Media on Students’ Learning Motivation in Thematic Learning for 5th Grade Science Content in Elementary Schools: Pengaruh Media Pembelajaran Video Terhadap Motivasi Belajar Peserta Didik pada Pembelajaran Tematik Muatan IPA Kelas 5 di Sekolah Dasar - Ristianti, Devi Darma; Istikomah, Istikomah (Indonesian Journal of Education Methods Development, 2022)
This study aims to analyze how the influence and how much influence video learning media has on students’ learning motivation in thematic learning of science content for class V at SDN Kemangsen 02 Balongbendo Sidoarjo. The research method used is a quantitative experiment with a Pre-Experimental design in the form of One-Group Pretest-Posttest. The sample of this research is class V-A and V-B SDN Kemangsen 02 with a total of 42 students. The sampling technique used was purposive sampling. Data analysis used a descriptive quantitative analysis approach to determine whether there were differences before and after treatment, so that it could be stated whether or not the treatment had an effect with the help of SPSS 16.0 for Windows. Based on the test results, it can be concluded that there is a significant effect between the use of video learning media on students’ learning motivation in thematic learning of science content for class V at SDN Kemangsen 02 Balongbendo Sidoarjo which has been proven through hypothesis testing (t-test) and the tcount value is 4,497. > t table 2.021 which means Ho is rejected and Ha is accepted. The level of influence is evidenced by the total pretest score of 82% with an average of 49.12 included in the less category while the total posttest score of 84% with an average of 50.40 included in the good category and evidenced by the R Squere value of 0.336 or 33, 6%. This means that the influence of video learning media on students’ learning motivation is 33.6%.